KARAKTERISTIK TEPUNG KECAMBAH KACANG NAGARA (Vigna unguiculata ssp Cylindrica) PADA SKALA KECIL DAN SCALE UP - Rini Hustiany; Noor Winda Wati; Emy Rahmawati; Alia Rahmi; Susi (Department of Agroindustrial Technology, Bogor Agricultural University, 2019)
South Kalimantan's pre-eminent cowpea, namely Nagara beans, needs to be improved, one of them being sprout flour. The purpose of this study was to (1) analyze the chemical and physicochemical properties of Nagara bean sprout flour on a small scale; (2) determining the best soaking and germination time on a small scale; and (3) comparing the chemical properties of Nagara bean sprout flour between small scale and scale up. The method used is making Nagara bean sprout on a small scale with an amount of 500 g, while on a scale up making sprout with an amount of 3000 g. Making sprouts on a small scale soaking for 12, 18, and 24 hours and germination for 24, 36, 42 and 48 hours. The germination for scale up is done with the best soaking and germination time of small-scale results, namely soaking for 12 hours and germination for 48 hours. The result is that soaking time only affects protein and carbohydrate content, whereas the interaction between soaking and germination time only affects the protein content of Nagara bean sprout flour. The best Nagara bean sprout flour is produced with a 12 hours soaking time and 48 hours germination time. Changes in the scale of the process of germination of Nagara bean sprout flour from small scale to scale up caused a decrease in levels of ash, protein and vitamin C content and an increase in levels of fat, carbohydrates, Fe, Ca, and vitamin E content. Keywords : Nagara bean, sprout, flour, small scale, scale up